2017
DOI: 10.1038/s41598-017-14131-3
|View full text |Cite
|
Sign up to set email alerts
|

Association between corneal endothelial cell densities and elevated cytokine levels in the aqueous humor

Abstract: Annual reduction rate of corneal endothelial cell density (ECD) varies among etiologies, however, the cause of chronic endothelial cell loss is still unknown. We recently reported the elevation of inflammatory cytokines in the aqueous humor (AqH) in eyes with bullous keratopathy and low ECD. To evaluate the association between ECD and aqueous cytokine levels, we collected a total of 157 AqH samples prospectively. The AqH levels of cytokines were measured and multivariate analyses were conducted to find the cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
26
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 41 publications
1
26
1
2
Order By: Relevance
“…Further, electron microscopy revealed that CEnCs in bullous keratopathy exhibited serious mitochondrial stress with severe loss of cristae and abnormal vacuolization. Recently, we showed that preoperative cytokine levels in AqH were correlated with CECD after corneal transplantation (8)(9)(10)(11), suggesting that the pathological microenvironment in AqH induces CEnC apoptosis. However, the exact mechanism remains elusive.…”
Section: Discussionmentioning
confidence: 99%
“…Further, electron microscopy revealed that CEnCs in bullous keratopathy exhibited serious mitochondrial stress with severe loss of cristae and abnormal vacuolization. Recently, we showed that preoperative cytokine levels in AqH were correlated with CECD after corneal transplantation (8)(9)(10)(11), suggesting that the pathological microenvironment in AqH induces CEnC apoptosis. However, the exact mechanism remains elusive.…”
Section: Discussionmentioning
confidence: 99%
“…ICAM-1 mediates the recruitment of immune cells to sites of inflammation, 44 and its soluble form, sICAM-1 has been shown to be increased in the AqH of patients with bullous keratopathy. 20,45 Richer et al 44 reported strong correlations between sICAM-1 and soluble apoptotic factors, such as soluble Fas and Fas ligand in rhegmatogenous retinal detachment. Recently, Dohlman et al 46 found that blockade of Eselectin suppressed graft rejection in murine corneal transplantation model, whereas both levels of E-selectin and Pselectin were upregulated in the rejected graft.…”
Section: Discussionmentioning
confidence: 99%
“…The suggested causes of endotheliopathy include penetration of PEX material towards the Descemet's membrane [28,29] and changes in the blood-aqueous barrier [30,31]. whereas the PEX group was significantly worse than the FECD group at 3 and 6 months (p=0.062 and 0.008, respectively; Mann-Whitney U test).…”
Section: Discussionmentioning
confidence: 99%